Biomechanical analysis of the hammer throw at the 2009 IAAF World Championships in athletics - Isele, R.; Nixdorf, E. (New Studies in Athletics, 2010)
The techniques of the top eight placers in the men`s and women`s hammer throw at the 2009 World Championships in Athletics were studied to obtain the latest data and insight into the technical condition of the world`s current best throwers. Video recordings of the best attempt of each thrower were analysed using a three-dimensional kinematographic measurement method.